PENGARUH CITRA PERUSAHAAN, KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA SMARTPHONE XIAOMI (Studi Kasus Pada Mahasiswa FE Universitas Sarjanawiyata Tamansiswa Yogyakarta) - Prasetyanto Prasetyanto (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe: (1) the influence of corporate image on customer trust (2) the influence of customer satisfaction on customer trust (3) influence customer confidence to customer loyalty (4) Influence of corporate image to customer loyalty (5) customer loyalty. This type of research is quantitative, population and sample in this study 100 students university sarjanawiyata tamansiswa yogyakarta with sampling technique purposive sampling. data collected by questionnaire method, data analysis technique used is multiple regression technique supported by T test, path analysis test and classical assumption test with help of SPSS 18.0 for windows application. The result of analysis shows that company image have positive and significant effect to customer trust with 0.000 <0,05 significance, customer satisfaction has positive and significant effect to customer trust with significance 0,015 <0,05, customer trust have positive and significant influence to customer loyalty with significance 0,035 <0,05, customer satisfaction have positive and significant effect to customer loyalty with significance 0.000 <0,05, personality influence to OCB with significance 0,013 <0,05, company image and customer satisfaction have positive and significant influence to customer loyalty with customer trust as intervening variable.